2013 13th International Conference on Intellient Systems Design and Applications 2013
DOI: 10.1109/isda.2013.6920726
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of Particle Swarm Optimization with adaptive genetic algorithm operators

Abstract: Particle Swarm Optimization (PSO) is a popular algorithm used extensively in continuous optimization. One of its well-known drawbacks is its propensity for premature convergence. Many techniques have been proposed for alleviating this problem. One of the alternative approaches is hybridization. Genetic Algorithms (GA) are one of the possible techniques used for hybridization. Most often, a mutation scheme is added to the PSO, but some applications of crossover have been added more recently. Some of these schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It can be applied for the form error evaluation, which contributes significantly to the production of mechanical components [29]. PSO can also be hybridized by combining with adaptive crossover and mutation rates [30] or by combining PSO with ant colony optimization (ACO) for convex and non-convex economic load dispatch (ELD) problem of a small scale thermal power system [31]. Also, a cooperative PSO (CPSO) is applied for solving function approximation and classification problems with improved accuracy [32].…”
Section: Introductionmentioning
confidence: 99%
“…It can be applied for the form error evaluation, which contributes significantly to the production of mechanical components [29]. PSO can also be hybridized by combining with adaptive crossover and mutation rates [30] or by combining PSO with ant colony optimization (ACO) for convex and non-convex economic load dispatch (ELD) problem of a small scale thermal power system [31]. Also, a cooperative PSO (CPSO) is applied for solving function approximation and classification problems with improved accuracy [32].…”
Section: Introductionmentioning
confidence: 99%
“…The time-vary approach use iteration number as a main factor of formulation while adaptive approach relies more on the PSO performances indicators such as particle fitness, global fitness and particle position. Details about the time-vary and adaptive formulations used in this papers are described in [25][26] respectively.…”
Section: Dynamic Parameterizationmentioning
confidence: 99%
“…The α is bounded within 0.1 times of the particle dimension. The algorithms have been previously tested on several benchmark functions [25][26] and the Vehicle Routing Problem with Time Windows (VRPTW) [28]. At this time, the interest has been coined to test the algorithms in Facility Layout Problem (FLP) [29].…”
Section: Fig7 Example Of Configuration For Sgcrossmutationmentioning
confidence: 99%
“…Previous experiments [35] that tested the time-vary and adaptive approaches on a set of well-known benchmark functions have found that the effective approach for time- vary is linear decreasing [25,36] and for adaptive is ISA [20] as presented in the following Figs 3 and 4. The benchmark functions are Sphere denoted as f 1 , Rosenbrock as f 2 , Rastrigin as f 3 , Levy as f 4 , Griewank as f 5 and Ackley's functions as f 6 .…”
Section: Selected Dynamic Parameterizationmentioning
confidence: 99%